Recent advances in SERS-based bioanalytical applications: live cell imaging - Lim, Dong-Kwon; Kumar, Panangattukara Prabhakaran Praveen (WALTER DE GRUYTER GMBH, 2024)
Raman scattering can provide information on molecular fingerprints, which have been widely applied in various fields of material science and nanobiotechnology. Notably, low interference with water molecules in obtaining the Raman spectra between 500 and 2000 cm-1 made it a powerful spectroscopic tool in biology, such as imaging and signaling for a living cell. To be a robust tool for cell biology, the performance of obtaining molecular-specific information with high sensitivity, high resolution in real time, and without inducing cell damage is strongly required. The conventional fluorescence-based method has been suffered from the rapid photobleaching of organic fluorophores and the lack of molecular information. In contrast, Raman scattering is a promising spectroscopic tool to acquire cellular information, and the extremely low signal intensity of Raman scattering could be amplified by incorporating the plasmonic nanomaterials. Along with the fundamental research focus on surface-enhanced Raman scattering (SERS), the practical approaches of SERS for cellular imaging as a new tool for drug screening and monitoring cellular signals have been extensively explored based on new optical setups and new designing strategies for the nanostructures. Diverse nanostructure and surface chemistry for targeting or sensing have been played pivotal roles in acquiring cellular information and high resolution cell imaging. In this regard, this review focused on the recent advances of SERS-based technologies for a live cell imaging investigated such as potential drug screening, signaling for chemicals or biomolecules in cell, in situ sensing, and high spatiotemporal resolution.